2023
DOI: 10.3389/fnut.2023.1042522
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary calcium and depression among American adults: National health and nutrition examination survey

Abstract: BackgroundThere is only limited evidence for an association between calcium (Ca) and depression, and the relationship was inconsistent. Therefore, the aim of this study was to assess the relationship between dietary Ca and the risk of depressive symptoms in individuals over the age of 18 in the US.MethodsWe extracted 14,971 participants from the US National Health and Nutrition Examination Survey (NHANES) 2007–2016 to probe their associations. Dietary Ca intake was measured through 24 h dietary recall method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…It is suggested that more attention should be paid to the intake of dietary calcium in daily diet, such as dairy products, dark green leafy vegetables, nuts, green beans and so on [ 31 ]. It can be taken in combination with foods rich in vitamin D [ 32 ], and more sun exposure is also one of the ways to promote calcium absorption [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that more attention should be paid to the intake of dietary calcium in daily diet, such as dairy products, dark green leafy vegetables, nuts, green beans and so on [ 31 ]. It can be taken in combination with foods rich in vitamin D [ 32 ], and more sun exposure is also one of the ways to promote calcium absorption [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of dietary calcium was obtained from the 24-h dietary recall questionnaire which was self-reported by the participants. Then the USDA’s Food Surveys Research Group (FSRG) encoded the data and calculated dietary calcium content according to their Food and Nutrient Database for Dietary Studies [ 19 ]. Blood samples were collected and stored in mobile devices by certified laboratory professionals.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary deficiencies in magnesium, zinc, selenium, copper, and manganese have been associated with a greater likelihood of depression [147][148][149][150][151][152][153][154][155][156][157][158][159][160]. Both excess and deficiency of copper and iron may affect the risk of depression [135,145,154,155].…”
Section: Mineral Componentsmentioning
confidence: 99%
“…Calcium plays a crucial role in many aspects of human health, including the formation and metabolism of bones, the activation of clotting factors, and the regulation of blood pressure and nerve functions [ 1 , 2 , 3 , 4 , 5 , 6 ]. Dietary calcium deficiency is a worldwide public health concern [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%